Penemuan Hukum oleh Hakim Mahkamah Agung Perspektif Hukum Progresif: Wasiat Wajibah Terhadap Anak Sebagai Ahli Waris Beda Agama - Abdul Jafar; Sarah Qosim; Syamsul Syamsul (Jurnal USM Law Review)
This study aims to analyze the progressive legal perspective on the considerations of judges in granting obligatory wills to non-Muslim heirs, uncover how this decision embodies legal discovery, and identify challenges and criticisms that arise both from Islamic law and positive law perspectives in Indonesia.In the progressive legal analysis, this decision demonstrates the courage of the Supreme Court judges in prioritizing substantive justice by considering the social context and pluralism of Indonesian society. The judges employed the method of ijtihad and Islamic jurisprudence principles to justify the granting of obligatory wills to non-Muslim children as a form of protecting human rights. However, this decision is not without criticism, with some arguing that the judges may have overstepped their authority and created legal uncertainty, particularly from the standpoint of conservative scholars who emphasize strict adherence to the texts of the Qur'an and Hadith. Additionally, challenges also arise from the perspective of positive law in Indonesia, concerning the judges' authority in creating precedents outside formal legislative mechanisms. These findings reinforce the urgency of developing more dynamic and responsive methods of legal interpretation to meet the needs of substantive justice. The impact of this decision shows that progressive legal discovery can set a precedent in Indonesia's legal practice, which, when applied prudently, can balance legal certainty and substantive justice. The study’s recommendations emphasize the importance of further discussions on the role of judges in harmonizing principles of justice with written law, as well as the application of legal discovery methods that support inclusivity and justice within a pluralistic society.